2022
DOI: 10.3389/fnut.2022.782430
|View full text |Cite
|
Sign up to set email alerts
|

SAlBi educa (Tailored Nutrition App for Improving Dietary Habits): Initial Evaluation of Usability

Abstract: In recent years, the use of applications to improve dietary habits has increased. Although numerous nutrition apps are available on the market, only few have been developed by health and nutrition professionals based on scientific evidence and subsequently tested to prove their usability. The main objective of this study was to design, develop, and evaluate the usability of a tailored nutrition application to be used to promote healthy eating habits. In order to decide app design and content, three focus group… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 67 publications
0
5
0
Order By: Relevance
“…SAlbi educa is a nutrition app, which provides tailored recommendations in order to balance the user’s diet. SAlbi educa’s usability in a real environment has been proven [ 25 ]. Additionally, the present study shows that SAlBi educa is a helpful tool for dietary counseling in primary healthcare for improving dietary habits.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…SAlbi educa is a nutrition app, which provides tailored recommendations in order to balance the user’s diet. SAlbi educa’s usability in a real environment has been proven [ 25 ]. Additionally, the present study shows that SAlBi educa is a helpful tool for dietary counseling in primary healthcare for improving dietary habits.…”
Section: Discussionmentioning
confidence: 99%
“…The present studies have shown the effectiveness of SalBi educa over one- and three-month periods. In a previous study, we evaluated adherence to SalBi educa for a one-month period, being 81.3% (participants who were tracking at least 3 days/week with two main eating occasions) [ 25 ]. Several studies have shown that nutrition apps present similar adherence at 6 and 11 weeks [ 64 , 65 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations